Australian and Southeast Asian Perspectives on China's Military Modernization. (August 2014) - Taneja, Pradeep
China's rapid military modernization has elicited a variety of responses from governments in the region. This article looks at the responses from Australia and two ASEAN states: Indonesia and Singapore. These states have been chosen because they have little or no territorial disputes with China that might influence their attitude towards China's military modernization. This article argues that China's military modernization is not driven solely by the pursuit of national reunification but has more to do with the nature of Sino-US competition and China's ambition to eventually replace the United States as the dominant power in the region. It is this competition that provides the rationale for Chinese military planners to seek to expand and modernize their military capabilities. And it is China's spectacular economic rise that provides the financial means toward that end. The United States, in turn, has responded with its 'pivot' to Asia to reassure its allies and partners in the region of its determination to maintain its hegemonic position in the region. But not all states in the Asia Pacific region have been equally worried about China's military modernization. In examining the responses of three different states with varying degrees of security links with the United States, this article will attempt to identify the similarities and differences in the way regional powers have responded to China's rise. In doing so, it will shed light on the future shape of the security order in East Asia.